Resposta:
#S: x in -oo; 0 uu 1 + sqrt2; + oo #
Explicació:
# 1 / x <= | x-2 | #
#D_f: x a RR ^ "*" #
per #x <0 #:
# 1 / x <= - (x-2) #
# 1> -x²-2x #
# x² + 2x + 1> 0 #
# (x + 1) ²> 0 #
#x a RR ^ "*" #
Però aquí tenim la condició que #x <0 #, tan:
# S_1: x a RR _ "-" ^ "*" #
Ara, si #x> 0 #:
# 1 / x <= x-2 #
# 1 <= x²-2x #
# x²-2x-1> = 0 #
#Δ=8#
# x_1 = (2 + sqrt8) / 2 = 1 + sqrt2 #
#cancel (x_2 = 1-sqrt2) # (#<0#)
Tan # S_2: x a 1 + sqrt2; + oo #
Finalment # S = S_1uuS_2 #
#S: x in -oo; 0 uu 1 + sqrt2; + oo #
0 / Aquí teniu la nostra resposta.